Observations on a Relationship between Steroid Metabolism and the Concentration of Plasma Fibrinogen - Amundson, B. A; Pilgeram, L. O (Thrombosis and Haemostasis, 1963)
Enovid (5 mg norethynodrel and 0.075 mg ethynylestradiol-3-methyl ether) therapy in young normal human subjects causes an increase in plasma fibrinogen of 32.4% (P >C 0.001). Consideration of this effect together with other effects of Enovid on the activity of specific blood coagulatory factors suggests that the steroids are exerting their effect at a specific site of the blood coagulation and/or fibrinolytic system. The broad spectrum of changes which are induced by the steroids may be attributed to a combination of a chain reaction and feed-back control.